2019
DOI: 10.1111/1462-2920.14856
|View full text |Cite|
|
Sign up to set email alerts
|

Mixed‐mode bacterial transmission in the common brooding coralPocillopora acuta

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 95 publications
3
53
2
Order By: Relevance
“…The results from this study have implications for future manipulation of the E. diaphana microbiome and perhaps that of corals. Recent studies have shown that cnidarians can acquire bacteria introduced into their external environment (Damjanovic et al, 2017(Damjanovic et al, , 2019b(Damjanovic et al, , 2020 and, with the addition of probiotic bacteria, may have the ability to mitigate the effects of climate change (Rosado et al, 2018). Future studies should test the ability of E. diaphana to acquire bacteria from their environment with a focus on microbes that have potentially beneficial traits for the holobiont.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from this study have implications for future manipulation of the E. diaphana microbiome and perhaps that of corals. Recent studies have shown that cnidarians can acquire bacteria introduced into their external environment (Damjanovic et al, 2017(Damjanovic et al, , 2019b(Damjanovic et al, , 2020 and, with the addition of probiotic bacteria, may have the ability to mitigate the effects of climate change (Rosado et al, 2018). Future studies should test the ability of E. diaphana to acquire bacteria from their environment with a focus on microbes that have potentially beneficial traits for the holobiont.…”
Section: Discussionmentioning
confidence: 99%
“…These potentially obligate anemone-associated taxa likely contribute to an important anemone feature like health or metabolism. The taxa we identified as stably associated with E. diaphana can be divided into those that are frequently found in cnidarians or their algal symbionts, including Alteromonadaceae (Rothig et al, 2017;Ahmed et al, 2019;Damjanovic et al, 2019a;Epstein et al, 2019b), Labrenzia (Lawson et al, 2017), Fulvivirga (Glasl et al, 2016;Ziegler et al, 2017;Epstein et al, 2019b;Pootakham et al, 2019;Damjanovic et al, 2020) and Sphingobacteriales (Meron et al, 2012;Kellogg et al, 2013;Li et al, 2014;van de Water et al, 2017;Bonthond et al, 2018), and those that occur much more infrequently, including Terasakiellaceae, Coxiella, and Nannocystaceae. Labrenzia is part of the core microbiome of the anemones' Symbiodiniaceae (Lawson et al, 2017) and may have a role in the production of antioxidants such as dimethylsulfoniopropionate (DMSP) and its breakdown products (Sunda et al, 2002).…”
Section: Potential Key Microbiome Members Of Exaiptasiamentioning
confidence: 99%
“…As more studies are being conducted, there are more evidences that do not necessarily support this idea ( Nussbaumer et al, 2006 ; Apprill et al, 2012 ; Leite et al, 2017 ; Björk et al, 2019 ; Oliveira et al, 2020 ). Many broadcast spawners pass their symbionts to their offspring by incorporating them into the mucus that envelops oocyte and sperm bundles ( Ceh et al, 2012 ; Ricardo et al, 2016 ; Leite et al, 2017 ) and a wide spectrum of mixed-mode transmission in brooders and in free and broadcast spawners is revealed ( Sipkema et al, 2015 ; Fieth et al, 2016 ; Bernasconi et al, 2019 ; Damjanovic et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…A critical characteristic in the selection of probiotic members is the maintenance and proliferation of the inoculated bacteria in the host over time [49] and their potential transmission to the next generation. There is evidence that corals release bacteria with their offspring such as Alteromonas [46], Flavobacteriaceae [46], Rhodobacteraceae [88], and…”
Section: Genes Of Interestmentioning
confidence: 99%